Ruqyah Syari'ah Counseling for Al Muhajirin Depok Congregation - Apipudin; Adi Artino; Rudi Iskandar (Jurnal Pengabdian Pancasila (JPP), 2023)
Popular treatment in Islam is ruqyah treatment. Understanding the ruqyah treatment method is very important to be understood by the community so that they can treat themselves personally and others. The main goal in community service is to provide an understanding of alternative Islamic psychiatric medicine through Ruqyah sharia. The method used is with workshops and intensive practical assistance to the community around the Al Muhajirin Limo Depok Mosque. The result: Increased understanding of sharia ruqyah is increasing in the Al Muhajirin Mosque Congregation in Depok. They are able to properly practice the mechanism or flow of sharia ruqyah treatment systematically and avoid things that are envious.